Baseline survey of sun protection policies and practices in primary school settings in New Zealand - Reeder, A I; Jopson, J A; Gray, A (Health education research, 2009)
The SunSmart Schools Accreditation Programme (SSAP) was launched as a national programme in October 2005 to help reduce the risk of excessive child exposure to ultraviolet radiation. As part of the need for evaluation, this paper reports the findings of a national survey of a randomly selected sample of approximately 12% of New Zealand primary schools prior to the national launch of the SSAP. Principals at 242 schools completed a mail survey (81% response rate) relating to school sun protection policies, practices, curriculum and environment. Survey responses were evaluated according to the 12 criteria of the SSAP, with schools assigned a score from 0 to 12. No school fully met all 12 accreditation criteria, although 2% of schools attained 11 criteria and another 2% attained 10. Nine per cent of schools attained three or fewer criteria. Overall, 7 was the most common score, achieved by 23%. School socio-economic decile rating and roll size were positively associated with higher scores (both P < 0.02). Continued support and resources are needed to encourage schools to address sun protection across the spectrum of curriculum, practices and environment and through commitment to written policy.